THE IMPORTANCE OF ENGLISH FOR THE STUDENTS OF AGRICULTURAL INSTITUTES - Hasanova Shahnoza Zohirovna (Galaxy International Interdisciplinary Research Journal, 2023)
Language refers to a method of communication that allows for greater comprehension and communication, and learners should be proficient in at least two languages. In reality, college students should acquire and be proficient in at least one foreign language, including reading, speaking, listening, and writing. Because English is the most vital language for international communication, it is taught in Uzbekistan from basic to university level. This detailed analysis depicts the English teaching method in Uzbekistan’s Agricultural Universities. Language is a required subject in all faculties at the undergraduate level. There are a few colleges that offer English as an optional subject, which is unusual. In this approach, communicative English has been selected for instruction. In the EFL classroom, 85% of teachers utilize a power point presentation and an overhead projector, while the rest use a white board and a marker.